Question
(4) \( 1+a-\frac{2 a-1}{2} \) (7) \( \frac{2}{x}+\frac{5}{x+1} \)
Ask by Gordon Zimmerman. in South Africa
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
Simplify the expressions:
1. \( 1 + a - \frac{2a - 1}{2} = \frac{3}{2} \)
2. \( \frac{2}{x} + \frac{5}{x + 1} = \frac{7x + 2}{x(x + 1)} \)
Solution
Certainly! Let's simplify each of the given expressions step by step.
---
### (4) Simplify \( 1 + a - \frac{2a - 1}{2} \)
**Step 1:** Combine like terms by expressing \(1\) and \(a\) with a common denominator.
\[
1 = \frac{2}{2}, \quad a = \frac{2a}{2}
\]
So,
\[
1 + a = \frac{2}{2} + \frac{2a}{2} = \frac{2 + 2a}{2}
\]
**Step 2:** Subtract the fraction \(\frac{2a - 1}{2}\):
\[
\frac{2 + 2a}{2} - \frac{2a - 1}{2} = \frac{2 + 2a - (2a - 1)}{2} = \frac{2 + 2a - 2a + 1}{2} = \frac{3}{2}
\]
**Final Simplified Form:**
\[
\boxed{\dfrac{3}{2}}
\]
---
### (7) Simplify \( \frac{2}{x} + \frac{5}{x + 1} \)
**Step 1:** Find a common denominator, which is \(x(x + 1)\).
\[
\frac{2}{x} = \frac{2(x + 1)}{x(x + 1)}, \quad \frac{5}{x + 1} = \frac{5x}{x(x + 1)}
\]
**Step 2:** Combine the fractions:
\[
\frac{2(x + 1)}{x(x + 1)} + \frac{5x}{x(x + 1)} = \frac{2x + 2 + 5x}{x(x + 1)} = \frac{7x + 2}{x(x + 1)}
\]
**Final Simplified Form:**
\[
\boxed{\dfrac{7x + 2}{x(x + 1)}}
\]
---
If you have any further questions or need additional explanations, feel free to ask!
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
To simplify the expression \( 1+a-\frac{2 a-1}{2} \), start by rewriting \( \frac{2 a - 1}{2} \) as \( a - \frac{1}{2} \). This leads to \( 1 + a - (a - \frac{1}{2}) = 1 + a - a + \frac{1}{2} = 1 + \frac{1}{2} = \frac{3}{2} \). For the expression \( \frac{2}{x}+\frac{5}{x+1} \), finding a common denominator is essential. The least common denominator is \( x(x+1) \). Rewrite the equation as \( \frac{2(x+1) + 5x}{x(x+1)} = \frac{2x + 2 + 5x}{x(x+1)} = \frac{7x + 2}{x(x+1)} \). Voilà! A beautiful rational expression that's primed for use.